Deciphering the interplay between psychopathological symptoms, sensorimotor, cognitive and global functioning: a transdiagnostic network analysis - Fritze, Stefan; Brandt, Geva A.; Volkmer, Sebastian; Daub, Jonas; Krayem, Maria; Kukovic, Jacqueline; Schwarz, Emanuel; Braun, Urs; Northoff, Georg; Wolf, Robert Christian; Kubera, Katharina Maria; Meyer-Lindenberg, Andreas; et al. (European archives of psychiatry and clinical neuroscience, 2024)
Understanding the relationship between psychopathology and major domains of human neurobehavioral functioning may identify new transdiagnostic treatment targets. However, studies examining the interrelationship between psychopathological symptoms, sensorimotor, cognitive, and global functioning in a transdiagnostic sample are lacking. We hypothesized a close relationship between sensorimotor and cognitive functioning in a transdiagnostic patient sample.
Online veröffentlicht: 20. März 2024
Gesehen am 20.11.2024